A Switchable Palladium(II) Trefoil Entangled Tetrahedron with Temperature Dependence and Concentration Independence. Issue 39 (23rd August 2022) - Algar, Jess L.; Findlay, James A.; Evans, Jack D.; Preston, Dan
Abstract: Self‐assembly makes metallo‐interlocked architectures attractive targets, but being in equilibrium with smaller species means that they can suffer from dilution effects. We show that a junctioned system gives rise to a [Pd4 (L)2 ] 8+ trefoil entangled tetrahedron irrespective of concentration. Heating the sample reversibly shifts the equilibrium from the knot to an isomeric non‐interlocked dual metallo‐cycle, demonstrating that thermodynamic equilibria can still be exploited for switching even in the absence of concentration effects. Abstract : A junctioned system has been developed that gives rise to a [Pd4 (L)2 ] 8+ trefoil entangled tetrahedron irrespective of the concentration. Heating the sample reversibly shifts the equilibrium from the knot to an isomeric non‐interlocked dual metallocycle, thus demonstrating that thermodynamic equilibria can still be exploited for switching even in the absence of concentration effects.